IDENTIFIKASI VARIETAS KENTANG SUPERJOHN BERDASARKAN PENANDA RAPD (Random Amplified Polymorphic DNA) - S., Runtunuwu D.; Rogi, J. E. X.; Palendeng, J. H. (EUGENIA, 2011)
Identification using morphological characters has time consuming. Currently, identification usingmolecular markers has now been popular due to rapid, saving time and more precisely. Superjohnpotato variety has been cultivated in North Sulawesi. However, the Superjohn potato variety has notbeen characterized using molecular markers. This research was aiming to identify â€•Superjohnâ€– potatobased on RAPD (Random Amplified Polymorphic DNA) markers. The research was conducted in fieldand laboratory. Field research was performed by taking some young leaves from â€•Superjohnâ€–, Granola,and Atlantic variety from the field. Identification using molecular marker was conducted at laboratory.Nine RAPD primers were used to identify the superjohn variety. The nine primers were OPA-1, OPA-2,OPA-3, OPA-4, OPA-5, OPA-7, OPA-9, OPA-10, and OPO-1. The molecular identification revealedthat â€•Superjohnâ€– variety was different with Granola and Atlantic. OPA-9700 primer could be used foridentification â€•Superjohnâ€– variety while OPA-101000 primer was suitable for identification Granolavariety.Keywords: Potatoes, variety, â€œSuperjohnâ€, Granola, Atlantic, and RAPDÂ ABSTRAKPenelitian ini dilakukan untuk mengidentikasi kentang â€•Superjohnâ€– berdasarkan penanda RAPD(Random Amplified Polymorphic DNA). Penelitian dilakukan di lapangan dan laboratorium. Penelitianlapangan dilakukan dengan mengambil beberapa daun muda dari varietas kentang â€•Superjohnâ€–,Atlantik dan Granola. Kemudian analisis DNA dilakukan di laboratorium menggunakan analisis RAPD.Berdasarkan penanda RAPD ternyata kentang â€•Superjohnâ€– berbeda dari kentang Granola dan kentangAtlantik. Penanda RAPD OPA-9700 dapat digunakan untuk mengidentifikasi kentangâ€•Superjohnâ€– danpenanda RAPD OPA-101000 dapat digunakan untuk mengidentifikasi kentang Granola.